Effects of seaweed waste on the viability of three bacterial isolates in biological fertilizer liquid formulations to enhance soil aggregation and fertility - Novi Arfarita; Takaya Higuchi; Cahyo Prayogo (Brawijaya University, 2019)
Biofertilizer production in Indonesia should fulfil the minimum requirement for being produced and released to the market. Problems occurred when those products are being absent on informing those expiration dates and the viability of microbial activity which then closely related to the quality of the product. Seaweed composted material are potential resources for producing Biofertilizer, but lacking on the optimization on their process as this material contain a various important component for soil and environment. The production of Biofertilizer from seaweed waste required an optimum condition, i.e.: pH and typical microbe which could germinate under specific formulation and temperature. This study aimed to determine the optimum pH in liquid fertilizer formulations made from seaweed waste in the form of composted material, to test the viability of three bacterial isolates and those pathogenicity properties, to examine the effect of metabolites release from bacterial isolates to green bean seed germination. The experimental design used was a completely randomized design with four treatments, which were as follow: P0 as a control (Peptone), RP1 (seaweed waste), RP2 (seaweed waste and glycerol), and RP3 (seaweed waste and PEG). The three bacterial isolates used were: (1) Bacillus licheniformis, (2) Psudomonas plecoglossicida and (3) Pantoea ananatis. This liquid fertilizer biological formulation was stored for 8 weeks at pH 5.5 and temperature 25oC. The results showed that the treatment of RP1 (seaweed waste) had high bacterial viability and could stimulate growth for green bean sprouts. The carrier material for seaweed waste with the addition of glycerol and PEG showed no effect of the disease and symptoms of a pathogenic bacterial consortium on germination of green beans.